Distribution of species in deep-sea biogeographic provinces and molecular phylogeny for the superfamily Neotanaoidea (Peracarida; Tanaidacea) indicate high levels of connectivity - Palacios Theil, Emma; Błażewicz, Magdalena (Frontiers in Marine Science, 2024)
Here we analyze available recorded occurrences for species of Neotanaoidea, a deep-sea peracarid superfamily, in the frame of biogeographic bathyal, abyssal, and hadal provinces. In addition, we provide the first phylogeny based on molecular data for this group. Despite the existence of large knowledge gaps, the observed patterns reveal levels of connectivity across biogeographic provinces, oceans, and depths higher than initially expected for a superfamily consisting of relatively small deep-sea benthic invertebrates without a pelagic larval stage, and therefore hypothetically low mobility capabilities. We have detected neotanaid species with closely related populations across the Pacific Ocean or able to overpass a geographical barrier as significant as the Mid-Atlantic Ridge. Additionally, the molecular analyses expose the need for a taxonomic review of the four genera within Neotanaoidea. A search for better suited morphological and possibly ecological characters as diagnostic traits for genera and species should be undertaken, aiming at a better definition of the existing taxa and the description of new ones. Despite them being found in all oceans at depths starting at 223 m (Neotanais antarcticus Kussakin 1967, www.obis.org, last visited 02 Feb 2024), neotanaids are not as often collected from the oceanic floor as other tanaidaceans and much is still unknown about their distribution patterns, life history, or behavior. They form a relatively diverse family represented currently by a total of 51 species, distributed among four genera: